(untitled) (American Journal of Pedagogical and Educational Research, 2023)
This article describes the effectiveness and challenges of online learning in rural areas. The findings of the study reveal that e-learning is a huge challenge for rural schools with a lack of online learning resources, skilled teachers, and so on.